Community Structure of Seagrass Meadows In Mantehage Island Waters, North Sulawesi - Simon I Patty; Husen Rifai (Sam Ratulangi University, 2013)
Research on the structure of seagrass communities in the waters of the island Mantehage was conducted in September 2010. The purpose of this study is to collect data and information on the structure of seagrass communities. Observations includes the identification seagrass species, measuring the number of individual/stand, cover percentage of each type/species on the transect. 6 types of seagrass found, i.e. Enhalus acoroides, Halophila ovalis, Thalassia hemprichii, Thalassodendron ciliatum, Cymodocea rotundata and Syringodium isoetifolium. Seagrass species composition and distribution varies at each location and is dominated by the presence of Thalassia hemprichii (48.14%) with coverage percentage ranges between 15.91% to 35.11%. Diversity index values ranged from 0.79 to 1.69 ; evenness index between 0.57 to 0.94 and the index of dominance between 0.20 to 0.56. In conclusion, the condition of seagrass meadows in Mantehage island is relatively good and can support marine life adequately.Keywords : Structure communities, seagrass, Mantehage Island